Explanation and Use of the Colposcopy Terminology of the IFCPC (International Federation for Cervical Pathology and Colposcopy) Rio 2011 - Quaas, J.; Reich, O.; Frey Tirri, B.; Küppers, V. (Geburtshilfe und Frauenheilkunde, 2013)
In July 2012 a revised terminology on colposcopic examinations of the cervix uteri was adopted by IFCPC. Central aspect is a description of characteristics that should aid in the definition of the disease entity cervix uteri. The nomenclature is built up in such a way that the examiner can evaluate colposcopic criteria according to a specific scheme. Firstly it is assessed whether the colposcopy is representative. Then it should be clarified whether or not the findings are normal. If the findings are not normal but rather abnormal the severity of the lesion is classified according to the so-called grade 1 (minor change) and grade 2 findings (major change). Specific abnormal findings such as leukoplakia, erosion and Lugolʼs finding are also not defined at this point. Characteristics suspicious for an invasion are described separately, in particular, atypical vessel patterns are mentioned here. As already held in the previous revised nomenclature (Barcelona), various findings are described in a last group: congenital transformation zones (CTZ), congenital anomalies, condylomas (papillomas), endometriosis, polyps (ectocervical, endocervical), inflammation, stenosis, postoperative changes (scarred portio, vaginal stump).
Keywords: colposcopy; cervix uteri; nomenclature; IFCPC Rio de Janeiro 2011